TRIZ-Based Approach in Co-creating Virtual Story-Maps - Narayanan, Kulathuramaiyer; Timothy, George Mintu (Springer Nature Switzerland, 2022)
TRIZ based models are particularly instrumental in formulating knowledge-based solutions in a variety of areas. The knowledge engineering capacity gained by systematic approaching problems according to the TRIZ structuring and modelling of problems, enables a powerful mechanism for drilling into the core conflicting or operating zone of the problem. This research then explores the knowledge engineering capacity of TRIZ to enable inventive solutions to solve even complex socio-technical problems. This paper presents a TRIZ-based methodology in the participatory design of shaping community-based virtual tourism programmes for indigenous communities living in the highlands of Borneo. In this paper, we demonstrate digital story-maps as a platform for unlocking tacit knowledge and giving indigenous communities a capacity to promote the uniqueness of their culture and heritage. Based on the initial TRIZ based framing of the problem, the use of digital story-maps has given rise to a systems-approach that has managed to bring out untold stories. These models have also supported the characterization of parameters of the virtual story-map solutions.